Tobacco use among young adolescents in Myanmar: Findings from global youth tobacco survey - Nyein Aye Tun; Thuzar Chittin; Naveen Agarwal; Mya Lay New; Yamin Thaung; Pyi Pyi Phyo (Indian Journal of Public Health, 2017)
Background: Tobacco consumption among youths poses significant public health problem in developing countries. This study utilized the available data of Global Youth Tobacco Survey (GYTS) to assess the prevalence of tobacco use among Myanmar adolescents. Objectives: We have conducted the fourth round of the GYTS in Myanmar during 2016 to monitor trends in tobacco use. Methods: We have selected 51 schools using random sampling based on probability proportional to school enrollment. In each school, we selected grades 9–11 by random sampling. All students in these classes completed a self-administered standard questionnaire. Results: A total of 3633 students who were participated in the survey 2621 students were 13–15 year. Overall 13.6% of students currently used tobacco; boys 26.3% and girls 3.7%. The prevalence of current cigarette smoking was 8.3%; boys 17.0%, girls 1.5%, whereas 5.7% of students currently smokeless tobacco users; boys 11.0%, girls 1.5%. Exposure to secondhand smoke (SHS) at home, in enclosed public places, and school was reported by 33.2%, 28.4%, and 64.5%, respectively. More than four out of 5 (83.4%) students had noticed someone using tobacco on television, videos or movies, and 42.3% had noticed tobacco advertising at points of sale. Among current smokers, 62.9% were not refused by purchasing cigarettes because of their minor age. Conclusion: Myanmar has higher prevalence of tobacco use among students, especially among boys. The study provides evidence-based information for developing comprehensive tobacco control programs – both education and policy interventions to reduce smoking rate among young people in Myanmar.